Germany : Financial Sector Assessment Program: Detailed Assessment of Observance of IOSCO Objectives and Principles of Securities Regulations. (IMF Staff Country Reports; Country Report, 2011)
Germany has a comprehensive legislative and institutional framework for the effective supervision of the securities markets. The overall level of compliance with the IOSCO principles is high. There are significant industry concerns about the implementation costs resulting from a rapidly changing legislative framework. The German Federal Financial Supervisory Authority (BaFin's) overall approach to supervision relies very heavily on the flow of information, auditors' reports, and compliance with legislative obligations. Regulators at both the federal and state levels work with a clear legal framework and clearly defined powers and responsibilities.